Thyroid hormone receptor beta (THRβ1) is the major regulator of T3 action in human iPSC-derived hepatocytes - Lorraine Soares De Oliveira; Joseph E. Kaserman; Anne H. Van Der Spek; Nora J. Lee; Hendrik J. Undeutsch; Rhiannon B. Werder; Andrew A. Wilson; Anthony N. Hollenberg (Molecular Metabolism)
Objective: Thyroid hormone (TH) action is mediated by thyroid hormone receptor (THR) isoforms. While THRβ1 is likely the main isoform expressed in liver, its role in human hepatocytes is not fully understood. Methods: To elucidate the role of THRβ1 action in human hepatocytes we used CRISPR/Cas9 editing to knock out THRβ1 in induced pluripotent stem cells (iPSC). Following directed differentiation to the hepatic lineage, iPSC-derived hepatocytes were then interrogated to determine the role of THRβ1 in ligand-independent and -dependent functions. Results: We found that the loss of THRβ1 promoted alterations in proliferation rate and metabolic pathways regulated by T3, including gluconeogenesis, lipid oxidation, fatty acid synthesis, and fatty acid uptake. We observed that key genes involved in liver metabolism are regulated through both T3 ligand-dependent and -independent THRβ1 signaling mechanisms. Finally, we demonstrate that following THRβ1 knockout, several key metabolic genes remain T3 responsive suggesting they are THRα targets. Conclusions: These results highlight that iPSC-derived hepatocytes are an effective platform to study mechanisms regulating TH signaling in human hepatocytes.